"Siyahamba": The Origins and Significance of a South African Chorus. Issue 2 (2nd July 2020) - Gorelik, Boris
Abstract: Despite the enduring international popularity of the Zulu Christian chorus "Siyahamba" as a song of protest and praise, South African ethnomusicologists have not yet investigated its origins as well as its cultural and political significance. This article reports the results of an historical study which indicated that the earliest documented performance of the chorus took place in Dundee in the current uMzinyathi district of the former Natal province (now KwaZulu-Natal or KZN), South Africa, in 1952. No earlier publications or handwritten records of its score or lyrics have been found. However, it appears that this musical work has a longer undocumented history, connected to rural Methodist or Pentecostalist communities of the province. It originated in a church environment as a devotional chorus and grew to be closely associated with the anti-apartheid movement after it was adopted by the international campaign against the racist regime from the mid-1980s. "Siyahamba" has been perceived both locally and internationally as a popular song of praise with a strong political significance thanks to the popular songbook Freedom Is Coming by Anders Nyberg, the Swedish-South African composer and choral conductor, who made the earliest known field recording of the chorus, and dozens of influential hymnals that include "Siyahamba". Chanted at rallies and public events, the historic South African tune continues to encourage campaigners for change worldwide.